Experimental Model of Myocardial Necrosis and Creation of Vascular Xenoprostheses for Regenerative Medicine - Chizh, Nikolay A.; Byzov, Denis V.; Shkand, Tatyana V.; Babaeva, Anna G.; Trofimova, Anna V.; Mikhaylova, Irina P.; Sleta, Irina V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2013)
N/AProbl Cryobiol Cryomed 2013; 23(4):368–372.